Environmental and microbial factors influence affective and cognitive behavior in C57BL/6 sub-strains - Abdel Aziz, Nada; Berkiks, Inssaf; Mosala, Paballo; Brombacher, Tiroyaone M.; Brombacher, Frank (Frontiers in Immunology, 2023)
C57BL/6 mice are one of the most widely used inbred strain in biomedical research. Early separation of the breeding colony has led to the development of several sub-strains. Colony separation led to genetic variation development driving numerous phenotypic discrepancies. The reported phenotypic behavior differences between the sub-strains were, however, not consistent among the literature, suggesting the involvement of factors other than the host genes. Here, we characterized the cognitive and affective behavior of C57BL/6J and C57BL/6N mice in correlation with the immune cell profile in brain. Furthermore, we dissected the contribution of microbial and environmental factors to cognitive and affective behavior pattern. We first noted a unique profile of locomotor activity, immobility pattern, and spatial and non-spatial learning and memory abilities between the two sub-strains. The phenotypic behavior profile was associated with a distinct difference in the dynamics of type 2 cytokines in the meninges and brain parenchyma. Using fecal microbiota transfer and mice co-housing techniques to analyse the contribution of microbiome and environmental factors to the noted behavioral profile, our data indicated that while the immobility pattern was genetically driven, locomotor activity and cognitive abilities were highly sensitive to alterations in gut microbiome and environmental factors. Changes in the phenotypic behavior in response to these factors were associated with changes in immune cells profile. While microglia were highly sensitive to alteration in gut microbiome, immune cells in meninges were more resilient. Collectively, our findings demonstrated a direct impact of environmental conditions on gut microbiota which subsequently alters brain immune cell profile that could modulate cognitive and affective behavior. Our data further highlight the importance of characterizing the laboratory available strain/sub-strain to select the most appropriate one that fits best the study purpose.